POLITIK DUALISME KURIKULUM PIAUD: STUDI KOMPARATIF KURIKULUM KEMENAG DAN KEMENDIKBUD DALAM IMPLEMENTASI LITERASI DINI - Uctuvia, Vina; Fajriyah, Euis; Wahyudin, Mohammad; Daryanto, Daryanto (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Early childhood education (ECE) serves as a critical foundation for children's literacy, language, and character development. In Indonesia, this foundational stage is complicated by a dual curriculum policy implemented by two ministries: the Ministry of Religious Affairs (Kemenag) and the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek). This study aims to critically analyze how early literacy is conceptualized in two official curricula—PAUD 2013 (Kemendikbudristek) and PIAUD 2020 (Kemenag)—through thematic content analysis and critical discourse analysis. The findings reveal that both curricula construct literacy within different ideological frames: the PAUD 2013 curriculum emphasizes scientific, play-based, and developmental approaches, while the PIAUD 2020 curriculum embeds religious values, character building, and Islamic traditions into literacy practices. This divergence creates pedagogical confusion at the implementation level, particularly in pesantren-based institutions that straddle both frameworks. The analysis also highlights how curriculum texts serve as ideological instruments, shaping educators’ practices through discursive constructions of knowledge, power, and morality. This study concludes that curriculum reform must move beyond technical alignment toward ideological integration, and recommends cross-ministerial training to bridge interpretive gaps among educators. The research contributes to the growing discourse on critical curriculum studies and educational policy in multicultural contexts.